Effect of statin use on clinical outcomes in ischemic stroke patients with atrial fibrillation. Issue 5 (February 2017) - Wu, Yi-Ling; Saver, Jeffrey L.; Chen, Pei-Chun; Lee, Jiann-Der; Wang, Hui-Hsuan; Rao, Neal M.; Lee, Meng; Ovbiagele, Bruce
Abstract : Abstract: It remains unclear whether statin therapy should be applied to ischemic stroke patients with atrial fibrillation. The objective of this study was to clarify whether statin therapy can influence the prognosis in recent ischemic stroke patients with atrial fibrillation. We identified ischemic stroke patients with atrial fibrillation between 2001 and 2011 from Taiwan National Health Insurance Database. Patients not treated with statins during the first 90 days after the index stroke were matched to patients treated with statins in the first 90 days in a 2:1 ratio on the basis of age, sex, hypertension, diabetes mellitus, ischemic heart disease, heart failure, estimated National Institutes of Health Stroke Scale, use of anticoagulant, and year of their entry into the cohort. The primary outcome was the first event of recurrent stroke, and the secondary outcome was in-hospital death. A total of 1546 atrial fibrillation patients with statin therapy in the first 90 days poststroke and 3092 matched atrial fibrillation nonstatin controls were enrolled for this analysis. During the median 2.4-year follow-up, the risk of recurrent stroke was not different between subjects receiving versus not receiving statin therapy (hazard ratios = 1.01, 95% confidence interval 0.88 to 1.15). However, patients with atrial fibrillation receiving statin therapy had a reduced risk for death during any hospitalization throughout the long-term follow-up period (hazard ratios = 0.74, 95% confidence interval 0.61 to 0.89). Among ischemic stroke patients with atrial fibrillation, statin therapy initiated during the acute to subacute poststroke stage did not alter the rate of stroke recurrence but was associated with a decreased rate of in-hospital death.